Effect of the herbicide Glyphosate on renal tissues in adult female rats - Hojat Karimi jashni (فصلنامه دانشگاه علوم پزشکی جهرم, 2013)
Introduction: Glyphosate is a herbicide with great toxicity, and is more commonly known as 'Roundup' and is formulated as isopropylamine salt. The aim of this study was to investigate the possible effects of the herbicide glyphosate on the renal tissue of female rats. Materials and Methods: 50 female rats were randomly divided into 5 groups of control, sham and experimental groups 1, 2, and 3. The three experimental groups 1, 2 and 3 received intraperitoneal glyphosate 50, 100 and 200 mg/ kg body weight daily for 14 days, respectively. Then, the rats were anesthetized and their kidneys were removed and weighted. Tissue section was prepared and studied by light microscope. Urea nitrogen, uric acid and creatinine in the blood were measured. Results: Proximal tubule diameter in groups 2 and 3 compared to that of the sham and control groups and distal tubule diameter in group 2 compared to that of the control group were significantly increased. Urea nitrogen, uric acid and creatinine levels Increased in the Experimental Groups. Other tissue changes such as lymphocytic infiltration, congestion of the kidney and renal cells damage in the experimental group 3 was harder than that of the groups 1 and 2. Conclusion: Glyphosate causes inflammation and damage to the renal tissue. So this herbicide should be handled with caution.